The Competitive Saving Motive: Concept, Evidence, and Implications - Shang-Jin Wei; Xiaobo Zhang (Asian Development Bank (ADB), 2015)
This short essay surveys recent literature on the competitive saving motive and its broader economic implications. The competitive saving motive is defined as saving to improve one's status relative to other competitors for dating and marriage partners. Here are some of the key results of the recent literature: (i) cross-country evidence show that greater gender imbalances tend to correspond with higher savings rates; (ii) household-level evidence suggest that: (a) families with unmarried sons in rural regions with more skewed sex ratios tend to have higher savings rates, while savings rates of families with unmarried daughters appear uncorrelated with gender imbalances; and (b) savings rates of families in cities tend to rise with the local sex ratio; (iii) rising sex ratios contribute nearly half of the rise in housing prices in the People's Republic of China; and (iv) families with sons in regions of greater sex ratios are more likely to become entrepreneurs and take risky jobs to earn more income.
hdl:11540/5272
Keywords: D1; E2; F3; I1; J1; J2; 330; competition; current account; saving; sex ratio